Which roads lead to depression in Latinas? A network analysis of prenatal depressive symptoms, discrimination, acculturative stress, and low birth weight. Issue 3 (28th January 2022) - Harris, Rebeca Alvarado; Chen, Daqi; Santos, Hudson P.
Abstract: Although immigrant mothers from some Latinx subgroups initially achieve healthy birth outcomes despite lower socioeconomic status, this advantage deteriorates across generations in the United States. Interpersonal discrimination and acculturative stress may interact with economic hardship to predict an intergenerational cascade of emotional and biological vulnerabilities, particularly perinatal depression. Network analyses may elucidate not only how and which psychosocial experiences relate to depressive symptoms, but which symptom‐to‐symptom relationships emerge. This study aims to understand (1) how economic, acculturative, and discrimination stressors relate to prenatal depression and low birth weight and (2) how Latinas may respond to and cope with stressors by exploring symptom–symptom and symptom–experience relationships. A sample of 151 pregnant Latinas (predominantly foreign‐born and Mexican and Central American descent) completed the EPDS and psychosocial questionnaires (discrimination, acculturation, acculturative stress, economic hardship) during pregnancy (24–32 weeks). Birth weights were recorded from postpartum medical records. We created network models using the Extended Bayesian Information Criterion Graphical Least Absolute Shrinkage and Selection Operator to estimate the relationship between variables. Discrimination exposure connected psychosocial stressors to depressive symptoms, particularly worry, crying, sadness, and self‐blame. Discrimination also revealed a connection between acculturation and low birth weight. Furthermore, younger age of migration and greater acculturation levels were correlated to greater discrimination stress and low birth weights. Perinatal research in Latinas must account not only for measures of cultural adaptation but recognize how developmental exposures across the life span, including discrimination, may be associated with adverse health trajectories for a mother and her child.